2018
DOI: 10.1111/vsu.12961
|View full text |Cite
|
Sign up to set email alerts
|

Articular cartilage lesions associated with complete lateral meniscal tears in the dog

Abstract: Objective To describe articular cartilage (AC) lesions associated with complete lateral meniscal tears in dogs. Study design Observational series. Animals Seventeen dogs with arthroscopic evidence of a complete lateral meniscal tear and associated AC lesions. Methods Medical records of dogs with arthroscopic evidence of complete lateral meniscal tear and associated AC lesions between March 2006 and December 2017 were examined for arthroscopic findings. Results The cranial cruciate ligament (CrCL) was intact in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
1
8
0
3
Order By: Relevance
“…The patient returned for reassessment after 15 days postoperatively, presenting complete clinical recovery with no claudication of the operated limb and no changes to the orthopedic examination, and was discharged from hospital. Krier et al (2018) suggested in their study that the complete lateral meniscal lesions are commonly isolated and present in dogs clinically similar to cranial cruciate ligament ruptures, in agreement to the reported in this case, in which the clinical manifestations were similar to the CCLR, and the suspicion of meniscal lesion appeared due to the absence of instability of the joint.…”
Section: Case Reportsupporting
confidence: 88%
See 1 more Smart Citation
“…The patient returned for reassessment after 15 days postoperatively, presenting complete clinical recovery with no claudication of the operated limb and no changes to the orthopedic examination, and was discharged from hospital. Krier et al (2018) suggested in their study that the complete lateral meniscal lesions are commonly isolated and present in dogs clinically similar to cranial cruciate ligament ruptures, in agreement to the reported in this case, in which the clinical manifestations were similar to the CCLR, and the suspicion of meniscal lesion appeared due to the absence of instability of the joint.…”
Section: Case Reportsupporting
confidence: 88%
“…Cranial cruciate ligament rupture is recognized as the main risk factor for the injury (VALEN et al, 2017). Loss of meniscus function and inflammatory cytokines secondary to rupture can result in joint cartilage damage (THIEMAN et al, 2009;SIHVONEN et al, 2016;KRIER et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…11 Meniskusrisse können so übersehen werden, vor allem auch im lateralen Gelenkskompartiment. 113,152 Ausserdem wird die Behandlung von Meniskusschäden und das Debridement der Kreuzbandreste durch den kleinen Zugang erschwert, wodurch das Risiko für Knorpelschäden steigt. 11 Zusammenfassend lässt sich sagen, dass die Arthroskopie momentan die präziseste und schonendste Methode für die Kniegelenksevaluation ist.…”
Section: Behandlungunclassified
“…13,158 Der laterale Meniskus kann sowohl isoliert erkranken, als auch in Kombination mit dem medialen Meniskus im Rahmen eines vKBR verletzt sein. 113,119,158,203 Ralphs et al, 2002 konnten bei 77% der arthroskopisch untersuchten Hunde mit vKBR Risse am lateralen Meniskus nachweisen. 158 Die klinische Signifikanz dieser lateralen Meniskusverletzungen ist jedoch noch nicht ausreichend geklärt.…”
Section: Behandlungunclassified
See 1 more Smart Citation